A LIFE-CYCLE INTERGENERATIONAL MODEL CONSIDERING SOCIAL SECURITY - Estulano Vieira, Beatriz; de Araujo Oliveira, João Gabriel; Nozaki Sugahara, Renato (Brazilian Keynesian Review, 2023)
The central objective of this paper is to deliver an intergenerational Life Cycle model considering the retirement process based on the pay-as-you-go system (PAYG). Our model is inspired by Baranzinis’ approach, where the optimal consumption analysis is made in a two-class type and restricted by the capital variation of each one. Our main results observe the equilibrium solution of the consumption and capital stock to both classes and conclude that the PAYG system does interfere with the results, as well as the time preference to leave or not inheritance. The methodology approached here is the Pontryagins’ Maximum Principle. We also applied a numerical simulation to ensure the robustness of our approach.